2017
DOI: 10.1097/ede.0000000000000606
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sample Handling and Analytical Procedures on Thyroid Hormone Concentrations in Pregnant Women’s Plasma

Abstract: Background Maternal thyroid function is a critical mediator of fetal brain development. Pregnancy-related physiologic changes and handling conditions of blood samples may influence thyroid hormone biomarkers. We investigated the reliability of thyroid hormone biomarkers in plasma of pregnant women under various handling conditions. Methods We enrolled 17 pregnant women; collected serum and plasma were immediately frozen. Additional plasma aliquots were subjected to different handling conditions before the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…laboratory. Study with similar results by Gro et al 16 conducted in Norway in 2017 showed that various handling conditions have no effect on TSH in plasma kept for up to 72-hours at room temperature. Recently Gang et al reported that although interpreting results of thyroid function tests becomes straight-forward but, it needs to be corelated with pre-analytical and post-analytical variables in order to improve efficacy and ignorance to these factors may lead to complications in patient's health 17 .…”
Section: S105supporting
confidence: 62%
“…laboratory. Study with similar results by Gro et al 16 conducted in Norway in 2017 showed that various handling conditions have no effect on TSH in plasma kept for up to 72-hours at room temperature. Recently Gang et al reported that although interpreting results of thyroid function tests becomes straight-forward but, it needs to be corelated with pre-analytical and post-analytical variables in order to improve efficacy and ignorance to these factors may lead to complications in patient's health 17 .…”
Section: S105supporting
confidence: 62%
“…Measurement of fT4 during pregnancy is complicated by pregnancy-related increases in thyroxine binding globulin concentrations, increased total thyroid hormone levels, lower levels of albumin in blood, and circulating human chorionic gonadotropin (hCG). 8688 The gold-standard method of measuring free thyroid hormones (which uses equilibrium dialysis as the first step, and which was used in one of the reviewed studies 51 ) can most accurately quantify fT4 levels during pregnancy, 80 but is costly. 87,89 All reviewed studies of maternal hypothyroxinemia, and all but one 51 study of maternal fT4, used immunoassays to assess fT4 rather than the gold-standard equilibrium dialysis approach.…”
Section: Discussionmentioning
confidence: 99%
“…Intra- and interassay CVs for T3, T4, and TSH were . We previously established the reliability of MoBa maternal plasma for measurement of thyroid hormone concentrations, considering delays in processing and storage and freeze-thaw cycles ( Villanger et al. 2017 ).…”
Section: Methodsmentioning
confidence: 99%